Effects of Organic Matters as Source of the Plant Growth Regulator on Seedling Growth of Mangosteen (Garcinia mangostana L.) - Berlintina, Duta; Karyanto, Agus; Rugayah; Hidayat, Kuswanta Futas (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2020)
Mangosteen (Garcinia mangostana L.) is one of the fruits that have a high potential in the market compared with other tropical fruit, mangosteen, but production is still very low. The main obstacle in the cultivation of mangosteen is slow growth due to lack of lateral roots, especially of plant origin mangosteen seeds. Therefore, efforts should be made to accelerate the growth of mangosteen seedling. This research aims to optimize the growth of mangosteen seedling, growth regulator technology using natural extracts of onion and sprouts extract with a different frequency of administration. The research was conducted in the greenhouse of Faculty of Agriculture, University of Lampung from October 2018 to March 2019. This study uses treatments arranged as factorial (2x3) in a randomized complete block design were repeated three times. The first factor is the type of extracts of onion and sprouts, and the second factor is the frequency of 1, 2, and 3 times. Data were analyzed by analysis of variance and the separation of the middle values ​​with orthogonal contrasts test at 5% significance level. The results showed that the giving of organic matter from the ZPT source one better in improving the mangosteen seedling fresh weight compared to the frequency of two or three times with the difference in weight of 0.47 g (12.71%). Mangosteen seedling root development is increased when treated with one application of sprout extract, but when using shallot extract two or three applications would be required.